Genetic diversity and prevalence of emerging Rickettsiales in Yunnan Province: a large-scale study - Chun-Hong Du; Rong Xiang; Shuang-Shuang Bie; Xing Yang; Ji-Hu Yang; Ming-Guo Yao; Yun Zhang; Zhi-Hai He; Zong-Ti Shao; Chun-Feng Luo; En-Nian Pu; Yu-Qiong Li; et al. (BMC, 2024)
Abstract Background Rickettsia and related diseases have been identified as significant global public health threats. This study involved comprehensive field and systematic investigations of various rickettsial organisms in Yunnan Province. Methods Between May 18, 2011 and November 23, 2020, field investigations were conducted across 42 counties in Yunnan Province, China, encompassing small mammals, livestock, and ticks. Preliminary screenings for Rickettsiales involved amplifying the 16S rRNA genes, along with additional genus- or species-specific genes, which were subsequently confirmed through sequencing results. Sequence comparisons were carried out using the Basic Local Alignment Search Tool (BLAST). Phylogenetic relationships were analyzed using the default parameters in the Molecular Evolutionary Genetics Analysis (MEGA) program. The chi-squared test was used to assess the diversities and component ratios of rickettsial agents across various parameters. Results A total of 7964 samples were collected from small mammals, livestock, and ticks through Yunnan Province and submitted for screening for rickettsial organisms. Sixteen rickettsial species from the genera Rickettsia, Anaplasma, Ehrlichia, Neoehrlichia, and Wolbachia were detected, with an overall prevalence of 14.72%. Among these, 11 species were identified as pathogens or potential pathogens to humans and livestock. Specifically, 10 rickettsial organisms were widely found in 42.11% (24 out of 57) of small mammal species. High prevalence was observed in Dremomys samples at 5.60%, in samples from regions with latitudes above 4000 m or alpine meadows, and in those obtained from Yuanmou County. Anaplasma phagocytophilum and Candidatus Neoehrlichia mikurensis were broadly infecting multiple genera of animal hosts. In contrast, the small mammal genera Neodon, Dremomys, Ochotona, Anourosorex, and Mus were carrying individually specific rickettsial agents, indicating host tropism. There were 13 rickettsial species detected in 57.14% (8 out of 14) of tick species, with the highest prevalence (37.07%) observed in the genus Rhipicephalus. Eight rickettsial species were identified in 2375 livestock samples. Notably, six new Rickettsiales variants/strains were discovered, and Candidatus Rickettsia longicornii was unambiguously identified. Conclusions This large-scale survey provided further insight into the high genetic diversity and overall prevalence of emerging Rickettsiales within endemic hotspots in Yunnan Province. The potential threats posed by these emerging tick-borne Rickettsiales to public health warrant attention, underscoring the need for effective strategies to guide the prevention and control of emerging zoonotic diseases in China. Graphical Abstract